Oriental arms and armour in the Hermitage Collection - Obraztsov, Vsevolod (The State Hermitage Publishers, 2015)
The book is devoted to the Hermitage collection of Oriental arms and armour which traces many centuries of arms production history in different regions of the East Turkey, Iran, India, Central and Southeast Asia, the Caucasus and the Far East. A significant part of the museum collection was formed in the first half of the 19th century and was based on the personal collection of Emperor Nicholas I. The collection continued to grow as a result of gifts from foreign rulers and diplomats, senior military officers and special acquisitions. It also included items seized as trophies in the numerous wars involving Russia in the countries of the East in the 19th century. A large number of these came from the arsenals of the conquered fortresses of Ardabil, Erivan, Erzurum and Adrianople, some were acquired from private collections. The book contains examples of different types of armaments, like armour, edged weapons and firearms, and spans a long chronological period from the late 15th to early 20th centuries. A focus is put on the decoration of the weapons. The book features Persian, Turkish, Caucasian, Indian and Japanese armaments with their unique shapes and ornaments dictated by national tradition. The edition is intended for historians, art historians, collectors, antique dealers and all art lovers.